Interpretasi Multikulturalisme Agama Dan Pendidikan - Erawati, Desi (Jurnal Studi Agama dan Masyarakat, 2017)
Multicultural of meaning can be understand various aspects of life , but more often come to the surface when touched by religious and multicultural education. Pluralist in about have a religion always touted though still much conflict do in the name of religion. In the world of education , just as the discourse of multicultural education, theory , concept , or the like is not on the level of the students have not his actions to realize in life should be. Conceptually speaking , should probably dig the meaning of multicultural local wisdom in the sphere of culture , in order to preserve the local culture and inheritance until not even left forgotten . Huma Betang is a special custom home Dayak tribe , meaning the philosophy contained in it is to appreciate , appreciate the diversity and united together. In this paper highlights how multicultural about have a religion can be understood in the domain and in the domain of education is not merely a matter of discourse but be applicable in understanding the life of nation and state .